2022
DOI: 10.1093/ecco-jcc/jjac057
|View full text |Cite
|
Sign up to set email alerts
|

A Narrative Systematic Review and Categorisation of Outcomes in Inflammatory Bowel Disease to Inform a Core Outcome Set for Real-world Evidence

Abstract: Background Heterogeneity exists in reported outcomes and outcome measurement instruments (OMI) from observational studies. A core outcome set (COS) for observational and real-world evidence (RWE) in inflammatory bowel disease (IBD) will facilitate pooling large datasets. This systematic review, describes and classifies clinical and patient-reported outcomes, for COS development. Methods The systematic review of MEDLINE, EMBAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…134 Similarly, a Swiss group 131 concluded in a systematic review based on 24 Crohn's disease and 25 ulcerative colitisstudies that maintenance biological therapies were not necessarily cost-effective, yet were associated with improved outcomes. In the future, cost-effectiveness studies need to be based on high-quality, real-world IBD cohorts to more accurately estimate disease outcomes 135 ; ideally, better estimates of indirect costs would also be used.…”
Section: Are the Data Sources Available Adequate To Assess Cost-effec...mentioning
confidence: 99%
“…134 Similarly, a Swiss group 131 concluded in a systematic review based on 24 Crohn's disease and 25 ulcerative colitisstudies that maintenance biological therapies were not necessarily cost-effective, yet were associated with improved outcomes. In the future, cost-effectiveness studies need to be based on high-quality, real-world IBD cohorts to more accurately estimate disease outcomes 135 ; ideally, better estimates of indirect costs would also be used.…”
Section: Are the Data Sources Available Adequate To Assess Cost-effec...mentioning
confidence: 99%
“…In general, this heterogeneity in use of outcomes and defining disease activity in RCTs, real-world evidence studies, and clinical practice in UC poses challenges not only for comparative research, but also for the way treatments are applied in clinical practice. 8 , 43 , 46 For example, a recent systematic review of RCTs identified six different scores used for classifying mildly-to-moderately active UC. 47 There is still no consensus on score cut-offs based on which disease severity is defined.…”
Section: Why May Early Escalation Of Biological Agents Lack Benefit I...mentioning
confidence: 99%
“…The OMI scale has been widely used-both spatially and temporally-among healthcare professionals' categories, as well as in various populations like undergraduate students, the general population, and psychiatric patients' relatives (48,49,52,53). Furthermore, the OMI scale has been commonly used in Greece, both for the general population (50,54), and for subpopulations, including students (51,(55)(56)(57)(58) and mental healthcare professionals (20,25,59,60).…”
Section: Opinion About Mental Illness Scale (Omi)mentioning
confidence: 99%